Avaliação dos lipídeos de membrana e das ORF's dos contratransportadores Na+/H+ e Na+/Ca2+ associados a mecanismos de adaptação à halofilia em Halococcus morrhuae - Assis, Priscilla Anne Castro de (2011)
Soil saliniy is a major factor in reducing plant growth and, consequently, their agricultural productivity. Most of the studies in the literature presents a strategy for reducing the effects of improving salt tolerance in plants for the production of osmolytes and stress proteins, and there are few studies aimed at increasing salt tolerance by restoring ionic homeostasis. This work was proposed to understand the physiological mechanisms and structural related with adjustment in the halophyle Halococcus morrhuae. This showed significant growth in the medium to halobacterias, that are organized in the form of sarcina of different sizes. The results achieved in attempts to characterize the lipid membrane halobactéria according to the values of retention time corresponding to phosphatidic acid (PA) and phosphatidylglycerol (C20-C20) (PG), and glycolipid known as Diglicosilarqueol (DGA-1 ). Additionally, patterns of breaks fatty acids extracted from Halococcus morrhuae showed a significant similarity when compared with the fatty acids found in organisms of the domain Eucarya and Bacteria. The genes of the antiport Na + / Ca2+ and Na + / H+ proved functional after cloning in Escherichia coli DH5α in solid and liquid medium. The antiport Na+ / H+ activity showed a statistically more significant when compared to the growth of clones containing the antiport Na+/Ca2+, making it interesting for the construction of transgenic plants tolerant to salinity. These database contribute to understanding the physiology of Halococcus morrhuae for future biotechnological applications, among them the inclusion of these genes in plants to assess the functionality in eukaryotic models.